A Drosophila mechanosensory transduction channel. - Walker, R.G.; Willingham, A.T.; Zuker, C.S. (Science, 2000)
Mechanosensory transduction underlies a wide range of senses, including proprioception, touch, balance, and hearing. The pivotal element of these senses is a mechanically gated ion channel that transduces sound, pressure, or movement into changes in excitability of specialized sensory cells. Despite the prevalence of mechanosensory systems, little is known about the molecular nature of the transduction channels. To identify such a channel, we analyzed Drosophila melanogaster mechanoreceptive mutants for defects in mechanosensory physiology. Loss-of-function mutations in the no mechanoreceptor potential C (nompC) gene virtually abolished mechanosensory signaling. nompC encodes a new ion channel that is essential for mechanosensory transduction. As expected for a transduction channel, D. melanogaster NOMPC and a Caenorhabditis elegans homolog were selectively expressed in mechanosensory organs.